PENGARUH KOMISARIS INDEPENDEN, KEPEMILIKAN INSTITUSIONAL, PROFITABILITAS, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP KETEPATWAKTUAN PUBLIKASI LAPORAN KEUANGAN TAHUNAN - Mahendra, Ida Bagus Kade Yogi; Asmara Putra, I Nyoman Wijana (E-Jurnal Akuntansi, 2014)
Normal 0 false false false EN-US X-NONE X-NONE One reliable reference as the basis for decision making can be given if the financial statements have relevant and reliable information. The loss of relevance of the information can reduce even eliminate the ability of the financial statements as a prediction tool for the users . The foregoing reflects the importance of timeliness annual financial statements to the public and the company is not expected to delay the presentation of its financial statements . The population in this study are all banking companies listed in Indonesia Stock Exchange 2009-2012. The number of samples used in this study was 92. Data analysis techniques used to solve this problem is binary logistic analysis. Based on the analysis results it is known that the independent commissioner , institusonal ownership as a proxy form of corporate governance and profitability, as well as the liquidity effect on the timeliness of the publication of the annual financial statements of banking companies listed in Indonesia Stock Exchange 2009-2012 . While the firm size has no effect on the timeliness of the publication of the annual financial statements of banking companies listed in Indonesia Stock Exchange 2009-2012
Keywords: timeliness, corporate governance, profitability, liquidity, size